Glial Cells Are Involved in ANG-II-Induced Vasopressin Release and Sodium Intake in Awake Rats - Flôr, Atalia F. L.; de Brito Alves, José L.; França-Silva, Maria S.; Balarini, Camille M.; Elias, Lucila L. K.; Ruginsk, Silvia G.; Antunes-Rodrigues, José; Braga, Valdir A.; Cruz, Josiane C. (Frontiers in Physiology, 2018)
It is known that circulating angiotensin II (ANG-II) acts on the circumventricular organs (CVOs), which partially lack a normal blood-brain barrier, to stimulate pressor response, vasopressin (AVP) and oxytocin (OT) secretion, as well as sodium and water intake. Although, ANG II type 1 receptors (AT1R) are expressed in neurons and astrocytes, the involvement of CVOs glial cells in the neuroendocrine, cardiovascular and behavioral responses induced by central ANG II remains to be further elucidated. To address this question, we performed a set of experiments combining in vitro studies in primary hypothalamic astrocyte cells (HACc) and in vivo intracerebroventricular (icv) microinjections in the lateral ventricle of awake rats. Our results showed that ANG II decreased glutamate uptake in HACc. In addition, in vivo studies showed that fluorocitrate (FCt), a reversible glial inhibitor, increased OT secretion, mean arterial pressure (MAP) and decreased breathing at rest. Furthermore, previous FCt decreased AVP secretion and sodium intake induced by central ANG II. Together, our findings support that CVOs glial cells are important in mediating neuroendocrine and cardiorespiratory functions, as well as, central ANG II- induced AVP release and salt-intake behavior in awake rats. According to our in vitro studies, we propose that these mechanisms are, at least in part, mediated by ANG II-induced astrocyte mediate reduction in glutamate extracellular clearance.